The Role of Gender in Job Crafting and Perceptions of Meaningful Work among Employees of PT X in Jakarta - Anugrah, Yohana Dian; Hunga, Arianti Ina Restiani; Wijono, Sutarto (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2025)
This study investigates the impact of gender variations on job crafting and the perceived meaningfulness of work among workers at PT. X, a digital consulting business in Jakarta. The survey included 55 employees, 40 men and 15 women, who completed a questionnaire on their job transitions and the significance of their roles. The findings indicated that male employees had a greater propensity to alter their employment in alignment with their preferences and competencies, maybe due to a perceived sense of autonomy. Employees who transitioned to new positions often perceived their roles as more relevant since this adjustment aligned their employment closely with their personal preferences. Notably, despite males changing occupations more frequently, there was no disparity between men and women regarding the perceived significance of their employment. The survey underscores the necessity for employers to assist all employees, particularly women, in advancing their careers through training, mentorship, and flexible work arrangements, ensuring that every employee feels empowered and respected.